Analisis Kebijakan Penyelenggaraan Pendidikan Ekstrakurikuler di Pondok Pesantren Minhajul Haq Purwakarta - Fadhilah Anggraini Pane; Eman Puroman (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
The implementation of extracurricular education in Islamic boarding schools plays a strategic role in shaping students’ character and developing their potential beyond the scope of intramural learning. This study employed a qualitative descriptive approach with data collected through observation, in-depth interviews, and documentation at Pondok Pesantren Minhajul Haq Purwakarta. Data were analyzed interactively through reduction, presentation, and conclusion drawing. The findings reveal that the extracurricular policy in this pesantren is designed to balance religious activities with the development of students’ interests and talents. Supervisors hold a central role in guiding programs and instilling values of discipline, responsibility, and collaboration. Academic activities such as the Math Club and Science Club enhance intellectual competence, while non-academic activities such as Pramuka, Tahfidz, and Archery nurture character, spirituality, and social skills. Challenges include limited human resources and facilities, whereas institutional support and supervisory commitment are key factors ensuring policy effectiveness. Overall, the implementation of extracurricular education policies at the pesantren contributes significantly to the development of students’ independence, leadership, and personal integrity